Prophylactic Use of Antiepileptic Drug (Phenytoin) in Preventing Early Postoperative Seizure in Patients with Chronic Subdural Hematoma: A Randomized Control Trial - Pradhanang, Amit Bahadur; Sedain, Gopal; Shilpakar, Sushil K.; Sharma, Mohan Raj (Indian Journal of Neurosurgery, 2019)
Introduction Antiepileptic drug (AED) therapy has been used prophylactically in various centers in patients with chronic subdural hematoma (CSDH) after surgical evacuation, although the benefit is unclear.Materials and Methods In this randomized controlled trial, patients with CSDH undergoing burr hole drainage were enrolled into two groups—one which received prophylactic phenytoin and the other without the drug use. Their clinical presentation, imaging findings and postoperative complications were analyzed. Primary objective of the study was to assess the efficacy of phenytoin in the reduction of early postoperative seizure.Results A total of 54 patients were enrolled in the study and randomized into two groups. Twenty-seven patients were assigned into the phenytoin group while another 27 patients to the “no phenytoin” group. Analysis of all patients in the no phenytoin group and those in the phenytoin group with therapeutic serum phenytoin levels were done. The incidence of postoperative seizure was 5.7%; and all patients who had seizures were in the no phenytoin group. This, however, was not statistically significant (p = 0.262). Two out of 25 patients on phenytoin (8%) developed adverse drug reactions.Conclusion Incidence of postoperative seizure in patients undergoing burr hole drainage for CSDH was low. Routine prophylactic use of AED, did not reduce seizure in early postoperative period.
Keywords: chronic SDH; phenytoin; seizure